Development of an IoT-Based Irrigation System for Animal Feed Corn Plots Development of an IoT-Based Irrigation System for Animal Feed Corn Plots: Development of an IoT-Based Irrigation System for Animal Feed Corn Plots - boonrom, panupong; Tarahom, Udomdet (RMUTL Journal of Socially Engaged Scholarship, 2025)
This study aimed to Develop an irrigation system for animal feed corn fields using Internet of Things technology, and Examine the performance and outcomes of using the IoT-based irrigation system in animal feed corn cultivation. The sample group consisted of 10 households from the Agricultural Productivity Enhancement Learning Center community network of animal feed corn growers, located in Khok Cham Rae Subdistrict, Thung Si Udom District, Ubon Ratchathani Province, covering a total cultivation area of 10 rai The research involved developing a demonstration learning center for an IoT-based Smart Farm irrigation system for animal feed corn, serving as a practical learning resource for farmers both within and outside the community. This center allowed participants to study and practice using the irrigation system in real agricultural settings The study results showed that the IoT-based irrigation system for animal feed corn fields led to: A 40% reduction in electricity consumption, An 80% reduction in farmers’ workload related to watering activities, and A 40% reduction in water usage. Furthermore, the use of the system provided farmers with more free time from routine farm tasks, enabling them to engage in additional income-generating activities such as organic fertilizer production, azolla (red fern) cultivation, cassava stem trading, and vegetable farming, which helped enhance household income and quality of life.